2017
DOI: 10.1136/bcr-2016-217268
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative OCT assisted descemetopexy with stromal vent incisions and intracameral gas injection for case of non-resolving Descemet's membrane detachment

Abstract: Descemet's membrane detachment (DMD) though uncommon in the present day scenario of advancing surgical techniques is a significant complication that requires prompt diagnosis and management. A middle-aged man presented to our hospital with poor gain of vision following cataract surgery. There was significant corneal oedema with DMD which was confirmed on anterior segment optical coherence tomography. We describe a modified continuous intraoperative-guided approach for the management of DMD in cases with oedema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Minor DMD may be resolved spontaneously for some time. 10 Minkovitz JB. et al found that DMD without scrolling is more likely to recover spontaneously, but with scrolling should be repaired early by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Minor DMD may be resolved spontaneously for some time. 10 Minkovitz JB. et al found that DMD without scrolling is more likely to recover spontaneously, but with scrolling should be repaired early by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…I-OCT could also be helpful in patients with ectopia lentis, preventing further corneal endothelium damage during lens removal [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…And it could be resolved successfully by giving her surveillance until 8 weeks after surgery. 5,9 Several retrospective analysis studies have found that descemetopexy represents a safe and effective option (reapplication in 71-87.5% of cases), which is why opting for this option emerged as the safest in view of the high postoperative success rate. 3,9 However, there is no solid evidence about which gas to perform Descemetopexy.…”
Section: Discussionmentioning
confidence: 99%
“…They can be classified into three types: simple, symmetric and complete detachment. 4,5 Most detachments are peripheral and resolve spontaneously, large and central DMD, if not treated properly, can cause decompensation and opacification of the cornea. 6 Recently, Kumar et al developed an algorithm for classifying and assigning DMD treatment called HELP (Height, extent, length and pupil) based on the dimensions of the DMD measured by AS-OCT and its extension based on 3 corneal zones that the authors delimited.…”
Section: Introductionmentioning
confidence: 99%